PROGRAM EDUKASI SARAPAN PAGI SEBAGAI UPAYA PENCEGAHAN MASALAH GIZI PADA SISWA SEKOLAH DASAR - Setyaningrum, Yahmi Ira; Utami, Bibit; Nur, Zilfi Fuadiyah (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
Skipping breakfast remains a common issue among school-age children in Indonesia. According to the Indonesian Health Survey (2023) and the Indonesian Nutrition Status Survey (2024), around 40–66% of Indonesian children do not have breakfast regularly, with East Java showing some of the highest rates. This condition affects nutritional status and learning concentration. To address this issue, a community service activity was conducted at SDN 02 Ngadilangkung on Monday, June 16, 2025, from 09.00 to 11.30 AM, involving 33 fourth-grade students. The aim of this activity was to improve students’ knowledge and awareness of the importance of a nutritious breakfast. The methods included lectures, group discussions, and interactive games using a puzzle box as an educational medium. Evaluation was carried out using pre-test and post-test, analyzed with the Wilcoxon test due to non-normal data distribution. The results showed a significant increase in students’ knowledge about breakfast, with the “good” category increasing from 65.4% to 84.6%. However, only a small portion of students regularly practiced balanced breakfasts. This program contributes to strengthening school-based nutrition education and promoting healthy habits from an early age.